1985
DOI: 10.1159/000199187
|View full text |Cite
|
Sign up to set email alerts
|

European Cooperative Crohn’s Disease Study (ECCDS): Colonoscopy

Abstract: 130 patients with Crohn’s disease were colonoscopied in a multicenter trial. The obtained data were analyzed with respect to gathering information on the inflammation pattern, as well as on the importance and prognostic value of special lesions in Crohn’s colitis. In 52 patients a second endoscopy was performed at the end of the 2-year study period. Ulcerations and aphthous lesions were the most common lesions, followed by pseudopolyps, cobblestone lesions and stenosis. In general, there was an increasing, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…The distribution of clinical manifestations in patients with different ana tomical involvement reported from other se ries [1,12] was largely confirmed by our results, although, with the exception of the association of perianal disease with colonic involvement, no specific pattern of clinical manifestations in patients with different ana tomical involvement was found. Endoscopic and histologic findings in the ECCDS pa tients are discussed in a separate paper [13],…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of clinical manifestations in patients with different ana tomical involvement reported from other se ries [1,12] was largely confirmed by our results, although, with the exception of the association of perianal disease with colonic involvement, no specific pattern of clinical manifestations in patients with different ana tomical involvement was found. Endoscopic and histologic findings in the ECCDS pa tients are discussed in a separate paper [13],…”
Section: Discussionmentioning
confidence: 99%
“…7 The exception is smoking, which is associated with an increased susceptibility for relapse and surgical intervention. 29,30 The endoscopic appearance of the mucosa seems to be of limited prognostic value after medically induced remission, 31 and repeated colonoscopy is an invasive procedure that is not indicated for CD patients on a regular basis. 31 In our previous studies in patients with steroidinduced remission, we found a weak correlation between splanchnic blood flow and endoscopic severity of disease in UC patients, but not in CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The endoscopic appearance of the mucosa seems to be of limited prognostic value after medically induced remission, 31 and repeated colonoscopy is an invasive procedure that is not indicated for CD patients on a regular basis. 31 In our previous studies in patients with steroidinduced remission, we found a weak correlation between splanchnic blood flow and endoscopic severity of disease in UC patients, but not in CD patients. 12,13 This difference has been confirmed in the current investigation of chronically active patients and may arise from the anatomic extent of inflammation in both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, among them the large multicenter studies of the European Cooperative Crohn's Disease Study (ECCDS) and National Cooperative Crohn's Disease Study (NCCDS), observed that the pattern of anatomical involvement has implications on the overall course of disease. The impression was given that colonic involvement, particularly with disease restricted to the colon, caused a worse overall outcome with more severe disease (1,2,(48)(49)(50)(51)(52).…”
Section: Clinical and Serologic Factorsmentioning
confidence: 99%